Medication adherence for secondary stroke prevention and its barriers among lebanese survivors: A cross-sectional study - Sylvia Saade; Rawan Kobeissy; Salwa Sandakli; Diana Malaeb; Nathalie Lahoud; Souheil Hallit; Hassan Hosseini; Pascale Salameh (Elsevier, 2021)
Objectives: Research assessing the adherence rate for clinical performance measures, compliance to medications for secondary stroke prevention as well as identifying barriers to medication adherence among stroke survivors has been conducted in many countries. However, to the best of our knowledge, to date no such research was performed in Lebanon highlighting the importance of our study. The study objective was to assess medication adherence for secondary stroke prevention among Lebanese stroke survivors and identify the barriers behind non-compliance. Methods: This is a cross-sectional study conducted among 100 Lebanese stroke survivors. Medication adherence and its potential barriers were assessed using the Lebanese medication adherence scale. Linear regressions were performed to identify factors independently related to medication adherence in stroke survivors. Results: A total of 83% of participants showed good adherence to medications; 27.3% of patients showed moderately severe disability and 67.3% suffered from fatigue. Both Mental and Physical Health Composite Scales indicated poor overall health related quality of life. A significantly higher mean medication adherence score was found in patients with social security insurance. However, patients with concerns about medications' side effects and cost were associated with a statistically significant lower adherence. Conclusion: The lack of social security insurance was the major barrier for medication compliance in Lebanese stroke survivors along with increased concerns about medications costs and side effects. Therefore, various strategies can further improve medication adherence for secondary stroke prevention in the Lebanese community.